Meningkatkan Kegiatan Keagamaan Di Mushola Desa Samuda Kecil - Ahmad Fazrianur; Bayu Hendrawan; Indri Kusuma; Siti Munilah; Munirah Munirah (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Religious activities in the mushola (small mosque) of Samuda Kecil Village are a strategic step in strengthening spiritual values and enhancing social solidarity within the predominantly Muslim community. The mushola serves as a vital center for worship and social interaction, yet community participation in religious activities still requires improvement to ensure the sustainability of these activities. Through the Community Service Program (KKN) by students of IAIN Palangka Raya Group 64, various religious activities were revived, such as teaching Quranic recitation, cleaning and repairing the mushola, leading prayers as imams, and calling to prayer as muezzins. The method used is Participatory Action Research (PAR), where students collaborate with the community in every phase of the activities, from problem identification to evaluation. The role of students as facilitators aims to encourage active involvement from community members, including children, teenagers, and adults, in religious activities at the mushola. The results show a significant increase in community participation, particularly in Quranic recitation classes, mushola cleanliness, and worship practices. This program not only strengthens the faith of the villagers but also fosters stronger social cohesion, making the mushola a more vibrant and sustainable spiritual center in Samuda Kecil Village.